Aspirations of the ilium and proximal femur increase the likelihood of culturing an organism in patients with presumed septic arthritis of the hip - Schmale, Gregory A. (J Child Orthop, 2015)
PURPOSE: To test the hypothesis that collecting material for culture from metaphyseal bone of the ilium and proximal femur at the time of a hip aspiration will increase the sensitivity to detect an infectious organism in patients with presumed septic arthritis of the hip. METHODS: We retrospectively reviewed a series of 36 patients with presumed septic arthritis of the hip, based on clinical exam and serum inflammatory markers, who underwent aspirations of hip synovial fluid as well as blood from the ilium and proximal femur. Culture results from aspirates of synovial fluid and bone and tissue from capsule were compared to determine the sensitivities and specificities of a synovial aspirate alone versus synovial aspirate plus aspirates of the ilium and proximal femur to detect infection. RESULTS: The sensitivity of hip synovial fluid aspirates to detect infection via positive culture was only 63 %, though this increased significantly to 100 % when the results of cultures of aspirates of the ilium and proximal femur were included. The specificities were equivalent in both modalities (≥90 %). We conclude that obtaining aspirates of the ilium and proximal femur at the time of hip synovial fluid aspiration increases the likelihood that the procedure will return an infectious organism. CONCLUSION: Positive cultures from a child with a septic hip or peri-articular hip infection help to efficiently and effectively guide antibiotic treatment. The child with a septic hip or peri-articular hip infection and positive cultures is likely to receive more narrow-spectrum therapy, potentially decreasing the overuse of broad-spectrum antibiotics. LEVEL OF EVIDENCE: DIAGNOSTIC STUDY LEVEL III: Development of diagnostic criteria on the basis of a series of non-consecutive patients (with universally applied reference “gold standard”).